Glioblastoma stem-like cells secrete the pro-angiogenic VEGF-A factor in extracellular vesicles. Issue 1 (1st December 2017) - Treps, Lucas; Perret, Raul; Edmond, Sébastien; Ricard, Damien; Gavard, Julie
ABSTRACT: Glioblastoma multiforme (GBM) are mortifying brain tumours that contain a subpopulation of tumour cells with stem-like properties, termed glioblastoma stem-like cells (GSCs). GSCs largely contribute to tumour initiation, propagation and resistance to current anti-cancer therapies. GSCs are situated in perivascular niches, closely associated with brain microvascular endothelial cells, thereby involved in bidirectional molecular and cellular interactions. Moreover, extracellular vesicles are suspected to carry essential information that can adapt the microenvironment to the tumour's needs, including tumour-induced angiogenesis. In GBM, extracellular vesicles produced by differentiated tumour cells and GSCs were demonstrated to disseminate locally and at distance. Here, we report that the pro-angiogenic pro-permeability factor VEGF-A is carried in extracellular vesicles secreted from ex vivo cultured patient-derived GSCs. Of note, extracellular vesicle-derived VEGF-A contributes to the in vitro elevation of permeability and angiogenic potential in human brain endothelial cells. Indeed, VEGF-A silencing in GSCs compromised in vitro extracellular vesicle-mediated increase in permeability and angiogenesis. From a clinical standpoint, extracellular vesicles isolated from circulating blood of GBM patients present higher levels of VEGF-A, as compared to healthy donors. Overall, our results suggest that extracellular vesicle-harboured VEGF-A targets brain endothelial cells and might impact their ability to form new vessels. Thus, tumour-released EV cargo might emerge as an instrumental part of the tumour-induced angiogenesis and vascular permeability modus operandi in GBM.